NKG2A/CD94 is a New Immune Receptor for HLA-G and Distinguishes Amino Acid Differences in the HLA-G Heavy Chain - Gia-Gia T. Hò (International Journal of Molecular Sciences, 2020)
Natural killer (NK) cell therapies are a tool to antagonize a dysfunctional immune system. NK cells recognize malignant cells, traffic to a tumor location, and infiltrate the solid tumor. The immune checkpoint molecule human leukocyte antigen (HLA)-G is upregulated on malignant cells but not on healthy surrounding cells, the requirement of understanding the basis of receptor mediated events at the HLA-G/NK cell interface becomes obvious. The NK cell receptors ILT2 and KIR2DL4 have been described to bind to HLA-G; however, their differential function and expression levels on NK cell subsets suggest the existence of an unreported receptor. Here, we performed a ligand-based receptor capture on living cells utilizing sHLA-G*01:01 molecules coupled to TriCEPS and bound to NK cells followed by mass spectrometric analyses. We could define NKG2A/CD94 as a cognate receptor of HLA-G. To verify the results, we used the reciprocal method by expressing recombinant soluble heterodimeric NKG2A/CD94 molecules and used them to target HLA-G*01:01 expressing cells. NKG2A/CD94 could be confirmed as an immune receptor of HLA-G*01:01. Despite HLA-G is marginal polymorphic, we could previously demonstrate that the most common allelic subtypes HLA-G*01:01/01:03 and 01:04 differ in peptide repertoire, their engagement to NK cells, their catalyzation of dNK cell proliferation and their impact on NK cell development. Continuing these studies with regard to NKG2A/CD94 engagement we engineered recombinant single antigen presenting K562 cells and targeted the surface expressed HLA-G*01:01, 01:03 or 01:04 molecules with NKG2A/CD94. Specificity and sensitivity of HLA-G*01:04/NKG2A/CD94 engagement could be significantly verified. The binding affinity decreases when using K562-G*01:03 or K562-G*01:01 cells as targets. These results demonstrate that the ligand-receptor assignment between HLA-G and NKG2A/CD94 is dependent of the amino acid composition in the HLA-G heavy chain. Understanding the biophysical basis of receptor-mediated events that lead to NK cell inhibition would help to remove non-tumor reactive cells and support personalized mild autologous NK cell therapies.